GA4GH Passport standard for digital identity and access permissions - Craig Voisin; Mikael Linden; Stephanie O.M. Dyke; Sarion R. Bowers; Pinar Alper; Maxmillian P. Barkley; David Bernick; Jianpeng Chao; Mélanie Courtot; Francis Jeanson; Melissa A. Konopko; Martin Kuba; et al. (Elsevier, 2021)
Summary: The Global Alliance for Genomics and Health (GA4GH) supports international standards that enable a federated data sharing model for the research community while respecting data security, ethical and regulatory frameworks, and data authorization and access processes for sensitive data. The GA4GH Passport standard (Passport) defines a machine-readable digital identity that conveys roles and data access permissions (called "visas") for individual users. Visas are issued by data stewards, including data access committees (DACs) working with public databases, the entities responsible for the quality, integrity, and access arrangements for the datasets in the management of human biomedical data. Passports streamline management of data access rights across data systems by using visas that present a data user's digital identity and permissions across organizations, tools, environments, and services. We describe real-world implementations of the GA4GH Passport standard in use cases from ELIXIR Europe, National Institutes of Health, and the Autism Sharing Initiative. These implementations demonstrate that the Passport standard has provided transparent mechanisms for establishing permissions and authorizing data access across platforms.